HUBUNGAN PENGGUNAAN GADGET DENGAN MOTIVASI BELAJAR SISWA DI SMP NEGERI 1 SIABU KECAMATAN SIABU KABUPATEN MANDAILING NATAL - Tedty Rohaya Tinambunan (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2020)
Excessive use of gadgets can make addiction so busy with himself not concerned with the surrounding environment can even affect his learning motivation. Based on data taken by DetikINET in 2014 showed that around 47 million Indonesians were active smartphone users or around 14% of all mobile phone users. Gadgets users in terms of age, early childhood and adolescents occupy a fairly high place, namely 79.9%. The research method used in this study is an analytical survey with a cross sectional approach. The sample in this study was 81 students, the research instruments used in this study were questionnaire / questionnaire and documentation. This research was conducted at 1 Siabu State Middle School, Kec. Siabu, Kab. Mandailing Natal from December 2018 to May 2019. The results of this study can be show that 79% of students use a gadget with a high category and 79% of students have less learning motivation. Based on the results of the study, it was found that there was a relationship between the use of gadgets and students' motivation in the 1 st of SMP Siabu. It can be seen from the significance value of the correlation 0.003 (p <0.05). It is recommended that students can be monitored and directed not to use gadgets excessively both at home and at school.